The influence of servant leadership on school quality through collaborative supervision and teacher performance - Yosepa, Rika; Komariah, Aan; Satori, Djam’an; Suharto, Nugraha (Universitas Jambi, Indonesia, 2026)
This research examines the influence of servant leadership on school quality by analyzing the mediating roles of collaborative supervision and teacher performance. This research employed a quantitative explanatory research design involving 41 respondents. The data were collected using a 71-item questionnaire measuring servant leadership, collaborative supervision, teacher performance, and school quality. Meanwhile, the data analysis was conducted through validity and reliability testing using SPSS and structural model analysis using SmartPLS 4 with bootstrapping of 5,000 subsamples. The results indicate that servant leadership significantly influences collaborative supervision and school quality. Collaborative supervision significantly affects teacher performance and mediates the relationship between servant leadership and teacher performance. In addition, teacher performance significantly contributes to school quality; however, its mediating effect between collaborative supervision and school quality, and the serial mediation pathway were not supported.